Considering capacity to use sex toys in secure care: two case reports. Issue 1 (9th February 2023) - Shaddel, Farshad; Mayes, Danielle
Abstract : The promotion and enabling of vulnerable and long‐stay inpatients' sexualities is a largely neglected practice. This paper offers a novel contribution to the existing literature by considering the assessment of capacity to use sex toys. It describes the development of a set of guidelines and application of these in two clinical cases. It is hoped that the paper will provide a start point from which the guidelines could be scrutinised and refined by professional bodies and legal review.